Symposium 3: Digital natives: Everyday life versus academic study - Corrin, Linda; Bennett, Sue; Lockyer, Lori (Proceedings of the International Conference on Networked Learning, 2010)
Access to and use of technology by ‘digital native’ students studying in our universities has been an area of much speculation, though relatively little empirical research. This has led some pundits to call for a radical rethink of how higher education uses technology to deliver education. Others are more circumspect and think it is necessary to hear directly from these ‘digital natives’ about their actual technology practices before jumping to such conclusions. This paper reports on a study that aimed to do just that; the study comprised a survey of the technology access and practices in both everyday life and for academic study of first year university students. The findings suggest that, for the participants of this study, access and usage of technology does not neatly fit into the stereotype of the ‘digital native’. Access to and use of some technologies was found to be quite high whilst others have significant levels of non-adoption. A comparison was made between technologies and activities undertaken as part of students’ everyday life in contrast to their academic study and it was found that the usage rates were generally lower for academic study. Access to and use of different technologies for different purposes is variable and university teachers and policymakers need to take this variability into account when making changes at the course or institution levels. What is also required is more in-depth investigation of the technology practices of these ‘digital natives’ to understand how technology is transforming their social and academic lives and, importantly, how they are shaping technology to suit their lives.